Validation study of the scale Child’s satisfaction with the diabetes nursing consultation - Pires, Anabela (2016)
Introduction: The implementation of quality in hospitals has stimulated the evaluation of user satisfaction, so the use of validated instruments is of extreme importance. Objective: To validate the scale “Child’s satisfaction with the diabetes nursing consultation”. Methods: Quantitative, cross-sectional and analytical study conducted in a non-probability sample of 135 children, average age of 13.45 years (SD= 2.83), who attend the diabetes consultation in 6portuguese public hospitals. An adapted version of the Users’ Satisfaction Scale with the Diabetes Nursing Consultation (Chaves et al., 2012) was used and it has made its psychometric study of scale. Results: The final factorial study presented 13 items distributed by 3 factors (Initial assessment, guidelines and relationship/ communication) that explain 49.95% of the total variance. The global adjustment indices were configured as good. The scale showed reliability of construct appropriate with composite reliability above 0.70 and reasonable convergent validity (approximately 0.50). The global Cronbach’s alpha coefficient proved good (α= 0.847). Conclusions: The results of the psychometric study let us consider this scale as an appropriate tool to use in studies in this context.